MAPPING THE LANDSCAPE: A BIBLIOMETRIC ANALYSIS OF COMPETENCIES AMONG ENTREPRENEURIAL EDUCATORS - Mansor, Farah Ahlami; Omar, Siti Nur Zahirah; Mat Jusoh, Yusri Huzaimi; Mohd Said, Nur Shafini; Mat, Khalid Amin (Journal of Islamic, Social, Economics and Development, 2024)
Entrepreneurship education is crucial for shaping the future of individuals and societies, providing learners with the skills, mindset, and knowledge to innovate, seize opportunities, and drive economic and social progress. It empowers individuals to foster innovation, create sustainable businesses, and advance the SDGs by promoting economic growth, reducing inequalities, and supporting sustainable development. By analyzing articles published in the Scopus database between 2018 and 2023, this study investigates publication patterns, identifies prominent authors, and explores citation metrics. The study provides insight into the scientific discussion on the competencies of entrepreneurial education, including the network on the co-occurrence of keywords, using VOSviewer. The data shows that scholars from all over the world have published 1276 articles. According to the data, 660 of the 1276 published documents (51.72%) come from articles as a source type. The data also shows that 32% of all articles originate from the social sciences. The article written by Neck H.M. and Corbett A.C. ranked first in terms of dissemination and was cited a total of 269 times by academics. The keyword trends were also used to identify further research topics for this theme. This study provides valuable insights into the academic discourse on the competencies of entrepreneurial educators, including the global research focus, leading academics, and influential institutions.